Geometric in Islamic art and design: infinite point or creativity through compass and digital - Hussin Ridzuan, Mokhtar Asmahan, Jantan Ramlan, (Universiti Pendidikan Sultan Idris, 2016)
Geometric in Islamic art and design: infinite point or creativity through compass and digital by Hussin Ridzuan, Mokhtar Asmahan, Jantan Ramlan,